The short- and long-term impacts of the COVID-19 pandemic on family farms in China – Evidence from a survey of 2 324 farms - Zhi-xiong DU; Xiao-dong LAI; Wen-jin LONG; Liang-liang GAO (Journal of Integrative Agriculture, 2020)
Family farms are considered the most desirable form of Chinese agriculture. Studies on the risk management of family farms are rare, while the COVID-19 pandemic provides an opportunity to explore how family farms respond to risks. Based on an online survey of 2 324 family crop farms, we examine for the first time the short-term impact (immediate impact or short-term fluctuation, and farms' instantaneous response) and long-term impact (on farms' future or long-term production) of the COVID-19 pandemic on family farms' production and operation in rural China. By using factor analysis and dummy variable regression, we find that the severity of the pandemic, the lockdown of the village, and farmers' knowledge of the pandemic contribute significantly to the short-term impact, but not on the long-term impact. Farmers' characteristics such as gender, age, and education are not related to the short-term impact, but family farms with male owners or owners with high school education or below are more likely to be diversified and large-scale. The number of years the farm has existed for and agricultural insurance affect both short-term and long-term impacts. We suggest that the government needs to pay more attention to stability-enhancing policies, the market environment, vocational training and the agricultural insurance market.